A preliminary study on the origin of human lung adenocarcinoma stem cells from lung bonchioalveolar stem cells - Biqiang ZHENG; Jin ZHOU; Qin GENG; Qianggang DONG (Chinese Journal of Lung Cancer, 2008)
Background and objective Lung adenocarcinomas are proposed to originate from the malignant transformation of bronchioalveolar stem cells (BASC). This hypothesis, however, has not been confirmed in humans yet.In the present study, we determined to analyze the BASC properties in human lung adenocarcinoma stem cells. MethodsThe human lung adenocarcinoma stem cells were obtained by flow cytometry (FCM) and induced with the sphereforming assay. The markers associated with BASC were measured by immunofluorescent staining, and their metastatic capacity was evaluated by injecting into NOD/SCID mice via tail vein. Results The majority of A549 and SPC-A1 humanlung adenocarcinoma cells expressed the type Ⅱ alveolar cell-specific marker SP-C. However, a minority of cells also expressed the bronchiolar Clara cell-specific marker CCSP and the embryonic stem cell marker OCT4, suggesting that these cells may belong to cancer stem cells with BASC properties. The CD24＋CD221＋ human lung adenocarcinoma stem cells were purified by FCM and then subjected to the immunofluorescent staining. The results documented that thesecells had the phenotype of CCSP＋SP-C＋OCT4＋, with the same phenotype as mouse BASC. Furthermore, the floatgrowing spheres (named pulmospheres) were developed after 2-week incubation of cancer cells in the serum-free medium containing EGF, IGF-1, and FGF-10. Again, the resultant pulmosphere cells had the phenotype of BASC. These cellswere able to differentiate when incubated for two weeks in serum-containing conditions, exhibiting the loss of CCSP and OCT4 markers. Animal studies indicated that the pulmosphere cells had the highly metastatic capacity. Conclusion The human lung adenocarcinoma stem cells may originate from the transformation of BASC, as their mouse counterparts. These primitive cancer cells are characterized to express the BASC markers as well as the embryonic stem cell gene OCT4 .